Kebijakan Pemerintah Daerah dalam Membangun Smart City di Kota Medan - Adi Suhendra; Arwanto H. Ginting (Research and Development Agency Ministry of Home Affairs, 2018)
This research is about local government policies in realizing smart city. This research is motivated by the existence of a new paradigm in governance and public services in local government as a way to improve good governance (Good Governance). The purpose of this research is to improve smart cities with policy innovation and technological innovation. This study uses a qualitative method. Triangulation of data sources is to explore the truth of certain information through various methods and sources of data acquisition. Observational researchers are involved (participant obervation), written documents, archives, historical documents, official records, notes or personal writings and drawings to produce different evidence or data. Whereas data processing researchers conducted data reduction. The reason for choosing this method is that this study is a contemporary social phenomenon / event. With this method, researchers can carry out observations and in-depth interviews with careful subjects. The results obtained in this study are in the management and development of smart city in the city of Medan, the city government has issued a regulation of Medan Mayor number 28 in 2018 concerning Smart city Kota Medan. the urgency of the guardianship formation is based on the development and synergy of all potential and integrated resources. Not only that, the Medan city government has also made a master plan for a smart city development roadmap to build integration between OPDs. The obstacles in reaching smart city are the uneven infrastructure and human resources to utilize ICT in the process of governance and public services. However, various efforts to overcome obstacles have also been prepared by taking into account the application infrastructure; human Resources; network infrastructure; information infrastructure, network integration, information and applications; funding; organizational structure, management system and work processes for better governance.